Development and characterization of a low-NOx partially premixed hydrogen burner using numerical simulation and flame diagnostics. (12th May 2023) - Schmidt, Nikolas; Müller, Marcel; Preuster, Patrick; Zigan, Lars; Wasserscheid, Peter; Will, Stefan
Abstract: The utilization of hydrogen as a fuel in free jet burners faces particular challenges due to its special combustion properties. The high laminar and turbulent flame velocities may lead to issues in flame stability and operational safety in premixed and partially premixed burners. Additionally, a high adiabatic combustion temperature favors the formation of thermal nitric oxides (NO). This study presents the development and optimization of a partially premixed hydrogen burner with low emissions of nitric oxides. The single-nozzle burner features a very short premixing duct and a simple geometric design. In a first development step, the design of the burner is optimized by numerical investigation (Star CCM+) of mixture formation, which is improved by geometric changes of the nozzle. The impact of geometric optimization and of humidification of the combustion air on NOx emissions is then investigated experimentally. The hydrogen flame is detected with an infrared camera to evaluate the flame stability for different burner configurations. The improved mixture formation by geometric optimization avoids temperature peaks and leads to a noticeable reduction in NOx emissions for equivalence ratios below 0.85. The experimental investigations also show that NOx emissions decrease with increasing relative humidity of combustion air. This single-nozzle forms the basis for multi-nozzle burners, where the desired output power can flexibly be adjusted by the number of single nozzles. Highlights: Design and numerical optimization of a partially premixed low-NOx hydrogen burner. NOx reduction: lean operation, humidified combustion air, geometrical optimization. Partially premixed hydrogen flame stability evaluation using infrared camera.